Artificial Intelligence and the Flipped Classroom: An Opportunity to Strengthen Active Learning in Medical Education. - Toala Mora, Ana Mikal (Spanish Journal of Medical Education, 2026)
The letter highlights the relevance of artificial intelligence and the flipped classroom as an innovative strategy for strengthening active learning in medical education. It analyzes their benefits in personalized learning and immediate feedback, as well as the challenges related to information quality and students’ critical thinking skills. Finally, it emphasizes the need for research to evaluate their impact on medical training.